Keaneragaman Tumbuhan Bawah Berpotensi Obat Di Jalur Pendakian Gunung Pundak - Purity Sabila Ajiningrum; Neka Alfaz Hanubah; Fernando Mulatua Hanumangan Gultom; Rika Aulia Wardani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2023)
This study aims to determine the diversity of medicinal plants on the Mount Pundak hiking trail. This research is quantitative descriptive research and data collection for this study used the plot method with a total of 8 plots at post 1 and 2 on the hiking trail with a size of 2m x 2m in each plot. Based on the results of observing the forest area of ​​the Mount Pundak hiking trail, there are 10 plant species in post 1 and 12 plant species in post 2. The total types of undergrowth that have medicinal potential are 16 types of data. This finding is based on a literature study on the analysis of medicinal plants. The species diversity index (H') in post 1 is 1.4530 and in post 2 (H') is 1.602, this shows that the diversity of medicinal plant species in the forest of Mount Pundak is moderate.